2016
DOI: 10.1371/journal.pone.0166564
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Butyrate Helps to Restore the Intestinal Status of a Marine Teleost (Sparus aurata) Fed Extreme Diets Low in Fish Meal and Fish Oil

Abstract: There is a constant need to find feed additives that improve health and nutrition of farmed fish and lessen the intestinal inflammation induced by plant-based ingredients. The objective of this study was to evaluate the effects of adding an organic acid salt to alleviate some of the detrimental effects of extreme plant-ingredient substitution of fish meal (FM) and fish oil (FO) in gilthead sea bream diet. Three experiments were conducted. In a first trial (T1), the best dose (0.4%) of sodium butyrate (BP-70 ®N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
112
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 61 publications
(68 reference statements)
5
112
0
1
Order By: Relevance
“…), while the potential beneficial effects of an SB (BP‐70 ® Norel) supplemented diet on the growth performance of gilthead sea bream ( S. aurata ) have been observed (Estensoro et al . ). Although both viscerosomatic and hepatosomatic indexes were not significantly altered, the gut index was significantly higher in fish fed on SB‐supplemented diet (0.8% BP‐70) compared to the other groups, the SB (0.4%) resulted in an increase in the plasma glucose and cortisol levels in gilthead sea bream (Estensoro et al .…”
Section: Application Of Scfas In Aquaculturementioning
confidence: 97%
See 3 more Smart Citations
“…), while the potential beneficial effects of an SB (BP‐70 ® Norel) supplemented diet on the growth performance of gilthead sea bream ( S. aurata ) have been observed (Estensoro et al . ). Although both viscerosomatic and hepatosomatic indexes were not significantly altered, the gut index was significantly higher in fish fed on SB‐supplemented diet (0.8% BP‐70) compared to the other groups, the SB (0.4%) resulted in an increase in the plasma glucose and cortisol levels in gilthead sea bream (Estensoro et al .…”
Section: Application Of Scfas In Aquaculturementioning
confidence: 97%
“…Although both viscerosomatic and hepatosomatic indexes were not significantly altered, the gut index was significantly higher in fish fed on SB‐supplemented diet (0.8% BP‐70) compared to the other groups, the SB (0.4%) resulted in an increase in the plasma glucose and cortisol levels in gilthead sea bream (Estensoro et al . ). Recently, Tian et al .…”
Section: Application Of Scfas In Aquaculturementioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, reducing arginine levels to 0.5% in the diet supplements signiicantly increased respiratory burst to levels comparable with control ish. In another study, Estensoro et al [113] showed that butyrate (BP-70 ® NOREL) helped to restore the intestinal status of marine gilthead sea bream (Sparus aurata) fed extremely low diets of ish meal (FM) and ish oil (FO). They observed that extremely low FO and FM diet levels signiicantly altered the transcriptomic proiles linked to nutrient absorption in the AI and increased expression of inlammatory, antioxidant, permeability and mucus production genes that coincided with increased granulocyte and lymphocyte presence in the PI submucosa.…”
Section: Nutrigenomics In Aquaculturementioning
confidence: 99%